Lymphoproliferative disease in a patient with Takayasu arteritis and ulcerative colitis. (2nd January 2019) - Asano, Yosuke; Sada, Ken-Ei; Hayashi, Keigo; Yamamura, Yuriko; Hiramatsu, Sumie; Ohashi, Keiji; Miyawaki, Yoshia; Morishita, Michiko; Watanabe, Haruki; Matsumoto, Yoshinori; Kawabata, Tomoko; Tanaka, Noriyuki; et al.
Abstract: Lymphoproliferative disorders (LPDs) are sometimes found in patients with autoimmune diseases receiving immunosuppressive treatments. However, LPDs in patients with Takayasu arteritis (TAK) were not reported previously. A 41-year-old woman with TAK and ulcerative colitis (UC) maintained remission with 5 mg/day of prednisolone (PSL) and 100 mg/day of azathioprine (AZA). However, the follow up colonoscopy showed reddish, submucosal lesion in the rectum, and histological examination revealed medium-to-large-sized atypical lymphocytes proliferating in the mucosal layer. These lymphoid cells were CD20 positive and Epstein–Barr encoding region (EBER) positive, demonstrating EB virus-associated LPD. After the diagnosis, AZA was discontinued and rituximab (RTX) was initiated for treatment of both LPD and TAK. A follow-up colonoscopy after three months showed no abnormal findings and the remission of both UC and TAK was maintained. As an increased risk of LPD has been reported in patients with inflammatory bowel disease receiving thiopurines, LPD in our case might be related with complication of UC and use of AZA. RTX might be one of the treatment options for cases with TAK complicating other iatrogenic immunodeficiency-associated LPD.